Influence of Changes in Soft Tissue Composition on Changes in Bone Strength in Peripubertal Girls: The STAR Longitudinal Study. (15th September 2020) - Bland, Victoria L; Bea, Jennifer W; Blew, Robert M; Roe, Denise J; Lee, Vinson R; Funk, Janet L; Going, Scott B
ABSTRACT: Obesity and osteoporosis remain two major public health concerns. Soft tissue composition and bone are interrelated; however, it is still not well understood how changes in adiposity during adolescence affect bone development. The aim of this study was to assess how changes in DXA‐derived total body lean mass (TBLM) and total body fat mass (TBFM) associate with 2‐year changes in bone outcomes at the 20% femur, 66% tibia, 66% radius, and 4% tibia, as measured by pQCT, during the years surrounding the onset of menarche in a cohort of 9‐ to 12‐year‐old (baseline) adolescent girls (70% Hispanic). From baseline to 2‐year follow‐up, girls showed statistically significant increases in all bone outcomes, except radial endosteal circumference. In separate linear regression models, change in TBLM and change in TBFM were both positively associated with 2‐year changes in bone outcomes at all measured bone sites, after controlling for relevant covariates. However, when change in TBLM and change in TBFM were included in the same model, change in TBLM was the predominant predictor of bone outcomes, explaining 4% to 14% of the variance in bone strength outcomes. Change in TBFM remained a positive predictor of tibia polar strength strain index (SSIp) (2% variance explained). A significant interaction between change in TBFM and menarcheal status was identified at the radius for SSIp and indicated that greater gains in TBFM were beneficial for SSIp in girls that were premenarcheal at baseline but detrimental for girls who were postmenarcheal at baseline. The overall findings suggest that changes in TBLM during the peripubertal years have a greater influence on bone outcomes than changes in TBFM. While gains in TBFM might benefit the weight bearing 66% tibia, greater gains in TBFM may be detrimental to bone development at the non‐weight bearing 66% radius after the onset of menarche. © 2020 American Society for Bone and Mineral Research (ASBMR).